Comparative Simulation Research on Stability of Layered and Homogeneous Surrounding Rocks. (November 2020) - Zhou, Heng; Huang, Peng; Di, Shengjie; Lu, Xi
Abstract: Layered surrounding rock mass is common in underground engineering, and it has obvious anisotropic mechanical properties. Therefore, the stability of the cavern excavation of layered surrounding rocks has always been a key issue in the engineering community. Based on an example of a hydraulic tunnel, the stability analysis of the excavation in cavern of the layered and homogeneous surrounding rocks are compared. The results show that the overall distribution of the stress field and displacement field of the layered and homogeneous surrounding rocks are basically the same. The stress field of the layered surrounding rocks has obvious discontinuous characteristics, and the deformation caused by excavation of the cavern is greater than the homogeneous surrounding rocks. The extent of the plastic zone along the joints of the layered surrounding rocks is also significantly larger than that of the homogeneous surrounding rocks.